Diagnosis of glioma brain cancer using visible resonance Raman spectroscopy - Zhou, Yan; Wu, Binlin; Liu, Chenghui; Yu, Xinguang; Cheng, Gangge; Wang, Kai; Zhang, Chunyuan; Shi, Lingyan; Alfano, R R (Frontiers in Optics / Laser Science (2018), paper JW4A.3, 2018)
Resonance Raman spectroscopy using 532nm excitation was used to distinguish normal brain tissue from different grades of glioma tissues. Principal component analysis was used to analyze the spectral data and achieved high accuracy. © 2018 The Author(s).
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/090-574-865-473-542
Keywords: Brain cancer; Brain tissue; Different grades; Glioma tissues; High-accuracy; Principal component analysis; Raman spectroscopy; Resonance Raman spectroscopy; Spectral data; Tumors; dept.phy

Assessment of basal cell carcinoma from normal human skin tissues using Resonance Raman spectroscopy - Liu, Chenghui; Wu, Binlin; Sordillo, Laura A; Boydstonwhite, Susie; Sriramoju, Vidyasagar; Zhang, Chunyuan; Beckman, Hugh; Zhang, Lin; Pei, Zhe; Shi, Lingyan; Alfano, R R (Frontiers in Optics, 2018)
VRR spectroscopy was used for BCC and normal skin tissues with 532nm excitation. The spectra showed significant changes in collagen, carotenoids and lipids. These enhanced fingerprints demonstrate a potential use as label-free pathology method. © 2018 The Author(s).
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-291-504-672-46X tex.type: [object Object]
Keywords: Basal cell carcinoma; Histology; Human skin; Label free; Normal skin; Resonance Raman spectroscopy; Tissue; dept.phy